Analysis of Market Concentration in Selected Sectors of Public Procurement - Svoboda Petr (Mendelova univerzita v Brně, 2016)
The goal of this article is the analysis of influence of market concentration in selected areas of public procurement on chosen parameters of public procurement in years 2007 and 2011. Five concentration ratios and five parameters of contracts are calculated for each of five chosen areas of public tenders in 2007 and 2011. After this task, the correlation analysis between concentration ratios and parameters of contracts is done for finding out mutual relation between these two variables. Correlation analysis is then compared with four created hypotheses about the relationship between market concentration and parameters of public procurement The results of the analysis are surprising, because in most cases, the stated hypotheses were rejected, meaning that the correlations between the parameters of public procurement and market concentration were different than this study predicted based on economic theory. The possible reasons for this result, discussed in the article, are corruption and also poor quality of data from Information system of public procurement administered by the Ministry for Regional Development of Czech Republic.
Analýza tržní koncentrace ve vybraných odvětvích veřejných zakázek
Keywords: concentration ratios; public tenders; parameters of contracts; analysis; correlation; koncentrační indexy; veřejné zakázky; parametry veřejných kontraktů:analýzy; korelace